Heterogeneous Models and Modelling Approaches for Engineering of Interactive Systems. Issue 1 (24th May 2021) - Aït-Ameur, Yamine; Bowen, Judy; Campos, José; Palanque, Philippe; Weyers, Benjamin
Abstract: This editorial introduces the special issue of Interacting with Computer on Heterogeneous Models and Modelling Approaches for Engineering of Interactive Systems. This special issue was proposed to gather the best contributions from a series of workshops organized alongside conferences such as FM'19 (3rd World Congress on Formal Methods) and EICS'19 (11th ACM SIGCHI Symposium on Engineering Interactive Computing Systems). It also encompasses papers submitted directly to this special issue.